Dietary diversity and meal frequency among infant and young children: a community based study - Aysheshim Kassahun Belew; Bekrie Mohammed Ali; Zegeye Abebe; Berihun Assefa Dachew (BMC, 2017)
Abstract Background Insufficient quantities, frequencies, and inadequate quality of complementary feedings have a negative effect on child health and growth, especially in the first two years of life. Therefore, the aim of this study was to assess the minimum dietary diversity, meal frequency and its associated factors among infants and young children aged 6-23 months at Dabat District, northwest, Ethiopia. Methods A community- based cross-sectional study was conducted from February 15 to March 10, 2016. The simple random sampling method was used to select study participants. An interviewer- administered structured questionnaire was used to collect data. Both Crude and Adjusted Odds Ratio with the corresponding 95% confidence interval were calculated to show the strength of association. In the multivariable analysis, variables with less than 0.05 P-value were considered statistically significant. Results The proportion of children who met the minimum dietary diversity and meal frequency were 17% (95% CI: 14.9, 19.4%) and 72.2% (95% CL: 69.3, 75%), respectively. Satisfactory media exposure (AOR = 2.79; 95% CI: 1.74, 4.47), postnatal care visits (AOR = 1.96; 95% CI: 1.32, 2.88), participation in child growth and monitoring follow ups (AOR = 1.65; 95% CI: 1.14, 2.39), age of children (AOR = 2.34; 95% CI: 1.33, 4.11) and age of mothers (AOR = 1.89; 95% CI: 1.09, 3.27) were positively associated with dietary diversity. Similarly, age of children (AOR = 2.38; 95% CI: 1.56, 3.65), household wealth status (AOR = 1.84; 95% CI: 1.27, 2.68), residence (AOR = 3.02; 95% CI: 1.41, 6.48), sources of information (AOR = 1.72; 95% CI:1.14, 2.59) and participation in child growth monitoring folow ups (AOR = 1.57; 95% CI: 1.13, 2.19) were significantly associated with meal frequency. Conclusion In this study, the proportion of children who received the minimum dietary diversity and meal frequency were low. Media exposure, age of children, postnatal care visits, and participation in child growth and monitoring follow-ups were significantly associated with dietary diversity. Likewise, wealth status and residence had a significant association with meal frequency. Thus, encouraging all mothers to participate in child monthly growth monitoring programs, intensive media advertising and strengthening counseling of mothers, and postnatal care visit are highly recommended for achieving the recommended dietary practices.